Electrical substations mapping for possible communication technologies using QGIS and Google Earth Pro - Izzati Thaqifah Zulkifli; Nayli Adriana Azhar; Nurul Asyikin Mohamed Radzi; Mohamad Faruq Syahmi Md Aripin; Kaiyisah Hanis Mohd Azmi; Faris Syahmi Samidi (Penerbit Universiti Kebangsaan Malaysia, 2024)
The visualization of mapping has aided researchers in gaining a better understanding and studying a specific area in a variety of professions. One of the well-known visualization software for mapping is the Geographic Information System (GIS). This work demonstrates the integration between an open-source GIS technology, named QGIS, and the Google Earth Pro programme in the mapping and analysis of electrical distribution substations. This integration shows the electrical substation data, the possible communication technology ranking, and a map that can be displayed and visualized based on the demographics. The QGIS in this study is used to reclassify the demographics into three main demographics: urban, suburban, and rural areas. On the other hand, the Google Earth Pro programme is used to map and visualize the overall electrical distribution substations alongside the communication technology ranking, based on the three main demographics. A case study using QGIS and Google Earth Pro was carried out in Area X, Malaysia for this investigation. Substation locations in Area X are mapped using Google Earth Pro, and the area’s demographics are categorized as part of the process. The features also enable the technology ranking to be displayed upon clicking the respective color-coded areas, where red represents urban area, yellow represents suburban and green represents rural This integration deems beneficial for future references on electrical distribution substations alongside the possible communication technologies